Acquiring High‐TC Layered Metal Halide Ferroelectrics via Cage‐Confined Ethylamine Rotators. (16th December 2020) - Peng, Yu; Bie, Jie; Liu, Xitao; Li, Lina; Chen, Shuang; Fa, Wei; Wang, Sasa; Sun, Zhihua; Luo, Junhua
Abstract: Two‐dimensional (2D) organic–inorganic hybrid perovskite (OIHP) ferroelectrics have attracted widespread interest in the field of optoelectronics due to the combination of excellent semiconducting and ferroelectric properties. The Curie temperature ( T C ), below which ferroelectricity exists, is a crucial parameter for ferroelectrics. However, the lack of research on T C tuning of 2D OIHP ferroelectrics hinders their further progress. Here, through incorporating ethylammonium (EA) as cage‐confined rotators, we obtained two 2D OIHP ferroelectrics, (IBA)2 (EA)Pb2 Br7 (2L ; IBA=isobutylammonium), and (IBA)2 (EA)2 Pb3 Br10 (3L ). Intriguingly, T C is successfully tuned from 326 K (2L ) to 370 K (3L ) with increasing layer thickness. Structural and computational analyses suggest that the improvement of T C is due to the higher phase‐transition energy barrier triggered by the cage‐confined EA rotators with increased layer thickness. This work suggests that EA is an effective "cage‐confined rotator" to rationally design high‐ T C 2D OIHP ferroelectrics. Abstract : By incorporating ethylammonium (EA) as cage‐confined rotators, two 2D organic–inorganic hybrid perovskite ferroelectrics were obtained: (IBA)2 (EA)Pb2 Br7 (IBA=isobutylammonium) and (IBA)2 (EA)2 Pb3 Br10 . Structural and computational analyses suggest that the improvement of the Curie temperature in these materials is due to the higher phase‐transition energy barrier triggered by the cage‐confined EA rotators with increasing layer thickness.